Scientific basis for predicting the spread of pests - A. Fedorenko; O. Borzykh; V. Fedorenko; V. Chaika; L. Yushchenko (Карантин і захист рослин)
Goal. To analyze the existing theories of mass reproduction of insects, to evaluate and test the established and newest methods of monitoring and prospects for their use in modern conditions of pest spread.